PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA BERBASIS PENDEKATAN SAINTIFIK DI KELAS IV MIS MADANI ALAUDDIN KABUPATEN GOWA - Fitriah , Nurul; Usman; Djafar, Hamsiah (Prodi PGMI IAI Sahid, 2025)
His research is development research with a research design using the 4-D development model developed by S. Thiagajaran & Semmel, namely: (1) definition stage, (2) design stage, development stage, and dissemination carried out in class IV MIS Madani Alauddin Gowa Regency. The data collection instruments used were LKPD validation sheets, learning outcomes tests and teacher response questionnaires. The research results can be described: First, the process of developing teaching materials using the 4-D development model developed by S. Thiagajaran & Semmel, namely: (1) the definition stage, there are several steps carried out at this stage, namely initial final analysis, student analysis, task analysis, concept analysis and formulating goals. (2) the design stage, there are several steps taken at this stage, namely media selection, format selection and initial design. (3) development stage, at this stage validation of expert lecturers and testing of teaching materials is carried out and (4) dissemination stage. Second, level of validity of teaching materials in the form of LKPD based on a scientific approach developed on poetry material in Indonesian subjects in class IV MIS Madani Alauddin Gowa Regency meets the valid criteria with an average of 3.54 (2.5 ≤V ≤4). Third, the level of effectiveness of teaching materials in the form of LKPD based on a scientific approach developed on poetry material for Indonesian language subjects in class IV MIS Madani Alauddin, Gowa Regency, obtained an average score of completeness of learning outcomes of 80% (85-100 = very high). The implications of the research in the form of developed products can be applied by educators in learning Indonesian in class IV MIS Madani Alauddin, Gowa Regency.